Gross and Biometrical Studies on Viscera of Black Buck (Antelope cervicapra) - kumari, Pinki; Panchal, K. M.; Vyas, Y. L. (Indian Journal of Veterinary Anatomy, 2013)
The filliform and fungiform papillae were scattered throughout the dorsum of the tongue. There were 25-28 vallate papillae arranged in a double row on either side. Curved, horny papillae called as unguiform papillae were present at the reticulo-omasal orifice. The liver was dark red in color and situated on the right side of the median plane. The pancreas was situated between the layers of mesentery to the right of median plane to the right of celiac and mesenteric arteries. It was irregularly quadrilateral in shape and weighed about 25.0 gm. The discoidal shaped spleen was attached to rumen by a gastro-splenic omentum and presented a retroperitoneal area towards its cranial margin. The hilus was present on the upper part of cranial border.